UPAYA PENINGKATAN KOMPETENSI PERSONEL DALAM PENATAUSAHAAN BARANG MILIK NEGARA (BMN) MELALUI PENGGUNAAN APLIKASI SIMAK-BMN DI AKADEMI MILITER MAGELANG - Wahyudianta, Eka; Widiastuti, Nur (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This research aims to describe personnel competency in administering state property (BMN) through the use of the Simak-BMN application at the Magelang Military Academy, to find out the causes of personnel competency in administering state property (BMN) through the use of the Simak-BMN application at the Magelang Military Academy. not yet optimal and to formulate efforts to increase personnel competency in administering state property (BMN) through the use of the Simak-BMN application at the Magelang Military Academy. The research design used is descriptive quantitative research supported by data obtained by observation, interviews and involvement with the research object. Data analysis uses the Miles & Hubberman qualitative analysis model. The results of the research show that personnel competency in administering state property (BMN) through the use of the Simak-BMN application at the Magelang Military Academy is still not optimal, due to limited understanding of the SIMAK BMN application, as well as limited human resources so they have to work simultaneously. Apart from that, they have different educational backgrounds in the technical field of Goods Administration.Efforts to increase personnel competency in administering state property (BMN) through the use of the Simak-BMN application at the Magelang Military Academy include competency development which can be carried out in the form of classical learning such as training, seminars, courses and upgrades as well as other activities carried out to maintain the level of expertise ( maintain rating) and non-classical learning is carried out, including through electronic learning programs (e-learning), guidance in the workplace, distance training, internships (on the job learning), as well as carrying out informal and formal coordination.